PRIORITY AREAS OF INVESTMENT ATTRACTIVENESS OF HOUSING CONSTRUCTION - Usmanov Mirumar Abdulla o’g’li (American Journals, 2024)
Stimulating the development of investment activity of enterprises of the investment and construction complex of the region is one of the ways to solve the problem of providing housing for the population. The article lists the main directions of activation of the process of attracting investment resources of construction organizations. The main problems of investment development in housing construction are presented. The authors propose their own options for simplifying state regulation in housing construction.
Keywords: Investment activity, social problems, housing sector, construction complex, development strategy, state regulation, antimonopoly committee, mortgage, capital, real estate market.